THE PHYSICAL CULTURE AND THE SCIENTIFIC RESEARCH - Borda Hurtado, Jaime (2014)
This study presents the development of scientific knowledge in different areas of Physical Culture and its educational and social implications, from a conception starting with the recognition of Sport and Physical Education practice as a fundamental right of human beings, acknowledged by the United Nations Organization, which proposes research outlines for the development of the Physical Culture.